Estudio comparado del Impuesto al Valor Agregado de los servicios religiosos de la Iglesia Católica en Ecuador, México y Colombia. - Cueva Cueva, Mercedes del Cisne (2022)
In this research a comparative study of the tax legislation of Ecuador, Mexico and Colombia on the Value Added Tax of religious services of the Catholic Church is carried out. In Ecuador, it is contemplated that the taxpayers of the Value Added Tax have the obligation to issue and deliver to the purchaser of a good or service an invoice or a sales receipt, situation that in reality is not so, since the Regulation for Application of the Law of Internal Tax Regime in its article 193 indicates that, for the rendering of religious services the issuance of sales receipts is not indispensable, This fact prevents the transparency of the economic activities of religious organizations, such as the Catholic Church, therefore a comparative study of Mexico and Colombia, countries where the issuance of sales receipts or invoices for the provision of religious services is mandatory, even in Colombia all activities that generate an economic income to religious organizations are subject to Sales Tax (VAT). In this comparative study, the materials and scientific tools necessary for its development were applied, a case study was also carried out to demonstrate the price of religious services of the Catholic Church, in addition to the analysis of statistical data that show that in the registration of the total income of the ecclesiastical parishes, the economic income obtained from the provision of religious services is omitted, It is also shown that the Catholic Church is the religious entity with more parishioners in Ecuador and therefore is the entity that provides more religious services to its faithful, which tend to be lucrative when a fixed price is demanded for its realization.